Enhancing Mathematical Problem-Solving and Teamwork Skills For Junior High Schools Student Through Project-Based Learning - Roza, Yenita; Murni, Atma; Adnan, Arisman; Alawiyah, Tuti; Gumanti, Gumanti (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
Problem-solving skills are not only correlated to academic success but also to increased competitiveness in a professional environment. However, many junior high school students have both weak mathematical problem-solving and teamwork skills. This study aims to describe the improvement of mathematical problem-solving and teamwork skills of students using the Project Based Learning (PjBL) model and scientific learning. This study is a quantitative study with a quasi-experimental method, using Pretest-Posttest Control Group Design. The population in this study consisted of 186 junior high school students in Bengkalis Regency. Data collection techniques were carried out through mathematical problem-solving ability tests and teamwork questionnaires. Data analysis was carried out using normalized gain (N-Gain) and one-way ANOVA. Based on the results of the data analysis, the results obtained were that students in the PjBL group showed a higher increase in problem-solving and teamwork skills with N-gains of 0.48 and 0.42, respectively, compared to the control class which obtained N-gains of 0.21 and 0.09, respectively. Teamwork skills consistently improved across all grades, while improvement in problem-solving skills varied according to students' initial abilities. This study supports existing research by integrating cognitive and affective aspects of problem-solving and financial literacy skills into everyday life.